Faith Interactions in Osogbo, Nigeria: A Muslim Perspective - Mumini O. Rauf; AbdulGafar Olawale Fahm (Millah: Journal of Religious Studies, 2022)
This paper examines the level of religious encounters among people of diverse faiths in Osogbo. It addresses the open exchange and interrelationship of adherents of different faiths within the city as well as the level of misunderstanding that exists from a Muslim perspective. The study is historical and descriptive. It is historical in the sense that it assesses newspaper reports, oral interviews, and court records while a descriptive approach was used in analyzing all the issues related to concepts and ideas of religious encounters. Â It reveals that the actions and inactions of people of other faiths in Osogbo are threats to social cohesion in the community. The study shows areas of conflict with the Muslims in Osogbo despite the open relationship among people of diverse faiths. The paper, therefore, recommends that for a good relationship to be sustained in Osogbo, there is a need for adherents of the three religions to keep off confrontational approaches and embrace dialogue and mutual understanding to promote peaceful co-existence within the community.